A happier life [large type] - Harvey, Kristy Woodson (Center Point Large Print, 2024)
"Present Day: Keaton Smith is desperate for a fresh start. So when her mother needs someone to put her childhood home in Beaufort, North Carolina, on the market -- the home that Keaton didn't know existed until now -- she jumps at the chance to head south. As she gets to know her charming next-door neighbor, his precocious ten-year-old son, and a flock of endearingly feisty town busybodies, she soon finds she has more questions than answers. 1976: After meeting her adoring husband Townsend, Rebecca "Becks" Saint James abandoned the life she knew and never looked back. Forty years later, she's made a name for herself hosting annual summer suppers that have become the stuff of legend, with locals and out-of-towners alike clamoring for an invitation to her stunning historic home. Becks strives to make the lives of those around her as easy as possible, but behind the façade she is facing a dilemma that even she can't solve. And as the end of the season looms, she is brought to a decision she never wanted to make. As both Keaton and Becks face new challenges and chapters, they are connected through time by the house on Sunset Lane, which has protected the secrets, hopes, and dreams of the women in their family for generations."--